Late complication of cutaneous filling after a facelift: a case report - Rafael Neves de Souza; Stenio de Godoy Mendoça; Ernani Coelho Alencar; André Luiz de Araújo França; Ênio Gomes de Araújo; Luiz Alberto de Sousa Leite (Revista Brasileira de Cirurgia Plástica, 2016)
The authors present the case of a patient who underwent a facelift with a chin implant 7 years after polymethylmethacrylate (PMMA) implantation, which evolved with foreign body granuloma in a region distant from the filling application. After nearly a year of treatment, the patient evolved with resolution of the granuloma.